Stakeholder Pressure, Green Innovation Practices And Organizational Performance: The Role Of Perceived Benefits As Moderator - Syed Ali, Sharifah Sabrina (2023)
This study also revealed that GI has a significant positive effect on the organizational performance. However, the moderation effect of perceived benefits is not significant. Thus, these findings provide a theoretical basis and reference for sustainable practices, particularly the substantial importance of GI in manufacturers for enhancing the organizational performance. It also shown the salient role of stakeholders in the implementation of GI practices and draws out various implications and policies for future research. As such, a distinct contribution was achieved by investigating and bringing together the antecedents, GI practices, and organizational performance and the role of perceived benefits as moderator in a single research framework. The practical contribution of this study imply that Malaysian manufacturers should efficiently and effectively implement GI practices to improve organizational performance when under pressure from customers, competitors, and suppliers.